PRODUKTIVITAS DAN EFISIENSI PEMANENAN KAYU DENGAN TEKNIK PENEBANGAN POHON SERENDAH MUNGKIN DI HUTAN PRODUKSI ALAM: STUDI KASUS DI TIGA PERUSAHAAN HUTAN DI KALIMANTAN TENGAH - Maman Mansyur Idris; Sona Suhartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
This paper presents the results of the study of wood harvesting productivity and efficiency when practicing the lowest possible felling technique. The case study was selected in three logging companies in Central Kalimantan in 1994. Then, the results are compared lo those obtained from conventional felling technique.the results of the study are as follow :1.The results of wood harvesting productivity is 25,2 m3/hr for lowest possible felling technique and 28,8 m3/hr for conventional felling. This difference is statisticallv significant.2.The average of wood harvesting efficiency is 86, 1 % for lowest possible felling technique and 82,1 % for conventional felling technique. This difference of 1,28 m3/tree is highl significant.3.The average of stwnp height when practicing the lowest possible felling technique is 0,45 m, while for conventional felling technique is 1,21 m.